The Clinical Outcomes of Preoperative Self‐Expandable Metal Stent Placement as Bridge to Surgery for Obstructive Colorectal Cancer - Ryosuke Aoki; Nao Hondo; Masato Kitazawa; Satoshi Nakamura; Makoto Koyama; Masahiro Kataoka; Hirokazu Tanaka; Takuya Iguchi; Yonghan Park; Yuji Soejima (Cancer Reports)
ABSTRACT Background Self‐expandable metal stent (SEMS) placement for obstructive colorectal cancer (OCRC) is widely performed as a bridge to surgery because of its lower mortality rate than emergency surgery. However, the long‐term outcomes remain unclear because of the risk of complications and cancer recurrence. This study investigated the short‐ and long‐term outcomes of SEMS placement for OCRC. Methods and Results We retrospectively reviewed the clinicopathological data of patients with OCRC who underwent preoperative treatment and tumor resection at our institution between April 2004 and March 2022. Among 113 patients with OCRC, 30 underwent SEMS placement (Group S) and 36 underwent ileus tube insertion (Group T); Group S had more older patients and fewer pT4 cases; no other characteristics differed. Incidence of severe complications was 0% versus 16.7% (p < 0.01); postoperative hospital stay was 14.3 versus 26.6 days (p < 0.01); medical costs were comparable between the groups. The long‐term outcomes of Group S and patients with non‐OCRC who underwent surgery during the same period were compared after propensity score matching. The 5‐year survival rates were 69.5% and 77.1%; the 5‐year recurrence‐free survival rates were 44.5% and 55.5%, without significant difference. Conclusion In conclusion, SEMS placement was more effective than ileus tube placement in treating OCRC.